SUSTAINABILITY ASSESSMENT OF AFFORDABLE HOUSING IN KUALA LUMPUR AND SELANGOR - Nurfarhani Rizal; Mohammad Zakri Tarmidi , (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Housing is a basic requirement that can improve one's standard of living. By balancing demand and supply, fostering an effective and sustainable housing sector, as well as providing efficient public facilities and services and a safe environment, the government is committed to ensuring access to quality and affordable housing to meet the needs of an increasing population. As a result, collaboration between the government and the private sector is critical in order to develop a competitive and long-term housing industry. The aim of this research is to enhance the spatial framework to measure the sustainability assessment of the affordable housing in Malaysia. The methodology of this study included both GIS and non-GIS analysis. The result of this study based on the spatial indicators nearby the affordable housing and the output of this study is the graph of the sustainability level of the affordable housing.